Inmate homosexual behavior in a southern female correctional facility - Koscheski, Mary (American journal of criminal justice, 2001)
Research concerning variables which impact inmate participation in same-sex sexual behavior within female correctional facilities is sparse. Data were collected via anonymous questionnaires from 245 inmates at a southern female correctional facility. Variables associated with same-sex sexual behavior among female inmates were prior homosexual behavior, younger age, and amount of time already served. Possible explanations for these findings are explored.